Properties of Fibrinogen Cleaved by Jararhagin, a Metalloproteinase from the Venom of Bothrops jararaca - Kamiguti, Aura S; Slupsky, Joseph R; Zuzel, Mirko; Hay, Charles R M (Thrombosis and Haemostasis, 1994)
Haemorrhagic metalloproteinases from Bothrops jararaca and other venoms degrade vessel-wall and plasma proteins involved in platelet plug and fibrin clot formation. These enzymes also cause proteolytic digestion of fibrinogen which has been suggested to cause defective platelet function. Fibrinogen degradation by jararhagin, a metalloproteinase from B. jararaca, and the effect of jararhagin fibrinogenolysis on both platelet aggregation and fibrin clot formation were investigated. Jararhagin was found to cleave human fibrinogen in the C-terminal region of the Aα-chain giving rise to a 285-290 kDa fibrinogen molecule lacking the Aα-chain RGD 572-574 platelet-binding site. Platelet binding and aggregation of ADP-activated platelets is unaffected by this modification. This indicates that the lost site is not essential for platelet aggregation, and that the remaining platelet binding sites located in the N-terminal portion of Aα chains (RGD 95-97) and the C-terminal of γ chains (dodecapeptide 400-411) are unaffected by jararhagin-digestion of fibrinogen. Fibrin clot formation with thrombin of this remnant fibrinogen molecule was defective, with poor polymerization of fibrin monomers but normal release of FPA. The abnormal polymerization could be explained by the loss of one of the two complementary polymerization sites required for side-by-side association of fibrin protofibrils. Jararhagin-induced inhibition of platelet function, an important cause of haemorrhage in envenomed patients, is not caused by proteolysis of fibrinogen, as had been thought, and the mechanism remains to be elucidated.